(untitled) (Journal of Applied Oral Science, 2012)
OBJECTIVES: The purpose of this study was to evaluate the antimicrobial activity of an acrylic resin combined with an antimicrobial polymer poly (2-tert-butylaminoethyl) methacrylate (PTBAEMA) to inhibit Staphylococcus aureus, Streptococcus mutans and Candida albicans biofilm formation. MATERIAL AND METHODS: Discs of a heat-polymerized acrylic resin were produced and divided according to PTBAEMA concentration: 0 (control), 10 and 25%. The specimens were inoculated (10(7) CFU/mL) and incubated at 37ºC for 48 h. After incubation, the wells were washed and each specimen was sonicated for 20 min. Replicate aliquots of resultant suspensions were plated at dilutions at 37ºC for 48 h. The number of colony-forming units (CFU) was counted and expressed as log (CFU+1)/mL and analyzed statistically with α=.05. RESULTS: The results showed that 25% PTBAEMA completely inhibited S. aureus and S. mutans biofilm formation. A significant reduction of log (CFU+1)/mL in count of S. aureus (control: 7.9±0.8A; 10%: 3.8±3.3B) and S. mutans (control: 7.5±0.7A; 10%: 5.1±2.7B) was observed for the group containing 10% PTBAEMA (Mann-Whitney, p